Framework para programas de competência em informação no ambiente universitário: uma proposta para o Sistema Integrado de Bibliotecas da Universidade Federal do Espírito Santo (Ufes) - Almeida, Eliéte Ribeiro (2023)
Information Literacy (IL) is essential for student teaching and learning, its emergence coincides with the advancement of Information and Communication Technologies (ICT) that influenced and drove many changes in society, including improviments in the educational field, the teaching and learning conditions. The development of this competence helps to improve knowledge, skills and attitudes related to the reflective discovery of information, its use and its dissemination in an ethical and responsible way. Carrying out programs of this nature in university libraries should be a planned and preferably institutionalized activity, forming part of the institution's teaching plan, in order to include all levels of student path. The problem of this research is based on understanding how the elaboration of a Framework for the development of information literacy in higher education can help in the structuring of educational actions developed in university libraries, having as universe the Central Library of the Federal University of Espírito Santo (BC/Ufes). Therefore, the overall objective was to develop a Framework for structuring an information literacy program within university libraries, based on the theories of the Association of College and Research Libraries (ACRL, 2016) and Santos (2020), the in order to specifically: a) contextualize the institutional scenario of the Central Library as coordinator of the Ufes Integrated Library System (SIB/Ufes); b) to verify the knowledge and perception of librarians in relation to the foundations and practices of Information Literacy; c) mapping the actions and services offered by the Central Library that are related to Information Literacy budgets; d) verify the contents related to the Information Literacy offered in the courses of the Central Library, according to the ACRL (2016) and with the dimensions of Vitorino and Piantola (2011). Thus, a descriptive-exploratory research with a qualitative approach was carried out, with preliminary bibliographic survey, case study and content analysis (Bardin, 2009). In addition, documentary research, questionnaire survey, interview and participant observation were used as support. Based on documentary research, the institutional scenario of BC/Ufes was contextualized, describing its characteristics and the educational activities offered. With the application of the questionnaire, it was demonstrated that librarians, in general, demonstrated satisfactory knowledge related to Informational Literacy, but there is a gap in relation to the practice of evaluating and disseminating this competence. In the interview, it was possible to verify that several educational actions related to Information Literacy are carried out in the library, however, there is no institutionalized practice. In the participant observation, it was verified that the actions carried out include contents that privilege the technical and ethical dimension, but are denoted components of other dimensions (VITORINO; PIANTOLA, 2011) and of aspects related to the knowledge practices of the ACRL (2016). Finally, a three-level framework for university libraries has been developed as a contribution to the practice of Information Literacy, offering librarians, information professionals, managers and teachers aids for: a plan to institutionalize, a plan to educate and a plan to learn.